Partial transformation from non-small cell lung cancer to small cell lung cancer: a case report and literatures review - Lu, Yicong; Fang, Danruo; Guo, Jiangying; Huang, Huaqiong (Frontiers in Oncology, 2025)
A fraction of lung adenocarcinoma patients with gene mutations who receive targeted therapy would experience acquired resistance and undergo small cell lung cancer (SCLC) transformation. The mechanisms behind the transformation of tumor pathological types and the treatment strategies are not fully clear. There have been case reports of the transformation from adenocarcinoma to SCLC, but the partial transformation from adenocarcinoma to SCLC has not been reported. We reported a case of a patient with partial transformation from lung adenocarcinoma to SCLC for the first time. The patient was diagnosed as lung adenocarcinoma with epidermal growth factor receptor (EGFR) 19 exon mutation and Tumor protein p53 (TP53) mutation. She received Epithelial growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) treatment. However, the tumor progression occurred and the lung aspiration pathology revealed a transformation from non-small cell lung cancer (NSCLC) to SCLC. The treatment regimen was changed to cisplatin and etoposide (EP) chemotherapy, resulting in a 2-month PFS. It was worth mentioning that adenocarcinoma cells were found in the patient’s emerging pericardial effusion, suggesting the co-existence of both adenocarcinoma and SCLC components. This is the first report of partial transformation from NSCLC to SCLC in the context of definitive pathology. It highlights that when no more pathological biopsy is feasible, we should be alert to the partial transformation and adopt the appropriate treatment.